Empowering The Magersaren Community: Technology Dissemination For Ground Coffee Added Value Improvement - Dewi, Ika Atsari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
The Magersaren community are farmers and forest workers who depend on forest for their livelihoods. Magersaren has been practicing agroforestry for a long time. They grow Robusta and Arabica coffee among other forest plants. Currently coffee is a favorite beverage, the number of its consumers continues to increase. The execution of community service activities that have been carried out consists of: 1)program socialization; 2)focus group discussion; 3)production, packaging and management training; 4)small-business starting up; 5)program evaluation. These community service activities are held during the social distancing due to the COVID-19 pandemic. This condition becomes an obstacle to the effectiveness of program implementation. The start-up small business needs to be continuously supported in order to survive through a critical period of business development, especially under economic pressure during the pandemic.